Rehabilitation in the dynamic stabilization of the lumbosacral spine - Calvosa, G.; Dubois, G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Until recently in the field of vertebral surgery, many diseases were managed with surgery of instrumented vertebral stabilization and bone fusion (arthrodesis). Fusion always offered valid and safe results, although at the expense of the abolition of the motility of the spine section which was being operated upon For this reason, when treating degenerative diseases of the lumbosacral spine, the Orthopaedic Clinic of the S. Chiara Hospital in Pisa, introduced the Dynesys® lumbosacral spine dynamic neutralization system to treat patients and spinal diseases with selected indications. Dynesys is a non-fusion elastic system with transpedicular screws and a flexible connector for dynamic stabilization. This is a new method for treating the degenerative disease of the lumbosacral spine which preserves motility at the treated levels. While allowing for movement of the segment at all levels, the Dynesys provides stability to the functional unit, which attains a condition of physiological function compared with the rigid stabilization-arthrodesis. This publication, which describes the indications and the various phases of technical rehabilitation to be used after surgical treatment of lumbar degenerative spine, represents a work of fundamental importance that is clearly useful to those interested in this area of orthopaedics. The pathologies treated are: disc bulging and micro-instability with lumbar pain and irritating sciatica; herniated disc and microinstability of one level with irritating lumbar-sciatic pain; spondylosis with stenosis affecting at least two levels; degenerative spondylolisthesis of one level up to grade 2; repeated surgery on a herniated disc at one or two levels; rotational scoliosis of moderate grade in adults.
Concepts of Biomechanics -- Vertebral Degeneration -- Surgical Treatment: From Stabilization-Arthrodesis to Non-Fusion -- Dynamic Stabilization with the Dynesys System -- Rehabilitation in Spinal Stabilization-Arthrodesis -- Rehabilitation in Dynamic Stabilization with the Dynesys System -- Conclusion -- References.
Keywords: Physiotherapy; Rehabilitation medicine; Physiotherapy; Rehabilitation Medicine